KETERLIBATAN UNITED STATES AGENCY FOR INTERNATIONAL DEVELOPMENT (USAID) DALAM MENGATASI MASALAH KEKERASAN BERBASIS GENDER DI INDONESIA TAHUN 2018-2021 - Sri Nurul Wahyuni; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This research analyzes the motives for assistance from the United States Agency for International Development (USAID) in overcoming the issue of gender-based violence in Indonesia in 2018-2021. This assistance is carried out through two programs, USAID Bersama and USAID eMpowering Access to Justice (MAJu). These programs are being implemented together with the Indonesian government, local organizations and independent institutions from Indonesia. This research is a qualitative research. The data collection methods used are interviews and document analysis. The perspective used is constructivism with foreign aid theory. The level of analysis used is the group level. This research looks for USAID's involvement in working to empower communities and change their mindsets around gender-based violence. Some of USAID's efforts are believed to be successful in supporting local organizations in improving Indonesian laws, as well on creating new new perspectives, knowledge and values. Keywords: USAID, gender-based violence in Indonesia, foreign aid policy.